Die verhouding tussen "poort" en "pad" in Matteus 7:13-14. 'n Oorsig van die moontlikhede - H. C. van Zyl (Acta Theologica)
The relationship between “gate” and “road” in Matthew 7:13-14 has always been a crux interpretum. There are basically three options in viewing the relationship. In the case of the first two the point of departure is that the metaphors differ in meaning; each metaphor therefore makes a unique contribution to the text. The two options are: the gate is at the beginning of the road, and the gate is at the end of the road. The third option regards the metaphors as synonyms, thus both conveying the same meaning. This option renders the relationship as of secondary importance.